Extraction, Cloning and Expression of RTB, as a Vaccine Adjuvant/Carrier, in E. coli and Production of Mouse Polyclonal Antibody (Anti-B chain Abs): Extraction, cloning and coxpression of RTB in E. coli and poly clonal antibody production. - Mohammad Sadraeian; Hossein Honari; Hamid Madanchi; Mahdi Hesaraki (Iranian Journal of Pharmaceutical Sciences, 2011)
Ricin, the toxic lectin extracted from the castor bean plant (Ricinus communis), consists of an A chain (RTA) and a B chain (RTB). Anti-A chain Abs and anti-B chain Abs can neutralize toxins in vivo and in vitro via blocking the binding of the toxin to the cell. Also, RTB protein is able to serve as an antigen deliver to the mucosal immune system and act as an immunoadjuant. Here, the genomic DNA was extracted from the fresh leave of the castor plant. The RTB gene was amplified by PCR. The prokaryotic expression vector pET-28a (+)- RTB was constructed, and used to transform E. coli Rosetta(DE3). The expression of recombinant protein induced by IPTG was examined by SDS-PAGE. Western blot were used to determine immunoreactivity of RTB-His by a rabbit monoclonal antibodies against His-tag. The SDS-PAGE profile exhibited the constructed prokaryotic expression efficiently produced RTB at the 1 mmol/L of IPTG. Addition of glycine and Triton X-100 enhanced native extracellular protein excreted into the culture medium. Anti-RTB polyclonal serum was generated by repeated immunization of mice with recombinant RTB protein. Finally, the antigenicity of recombinant RTB was identified by Western blot and indirect ELISA. A relative high titer of anti-RTB antibody was detected after the fourth injection. Western blot analysis was carried out with the polyclonal antibody revealed almost a 32-kDa band which corresponds to RTB protein. In conclusion, we herein report the expression of fully biologically active RTB as a plant lectin by a new strategy. This recombinant Ricin protein could be a promising drug for cancer therapy, vaccine as an immune response enhancement and even viral infected cells.